A Systematic Literature Review: Exploring Leadership and Organizational Factors Driving Innovative Work Behavior in SMEs - Tsabita Khwarazmita (Cita konsultindo, 2024)
This systematic literature review explores the relationship between transformational leadership and innovative work behavior (IWB) in small and medium enterprises (SMEs). The review identifies how transformational leadership fosters an environment conducive to employee innovation through intellectual stimulation, individualized consideration, and inspirational motivation. Key mediators like knowledge sharing and perceived organizational support enhance this relationship, creating a collaborative culture that empowers employees to generate and implement new ideas. The review also highlights other critical variables influencing IWB, including organizational justice, psychological capital, and a learning-oriented organizational culture. These variables act as mediators or moderators, further shaping employees' innovative capacities. Findings from the VOSviewer analysis reinforce the central role of transformational leadership in driving innovation within SMEs and emphasize the importance of a supportive organizational culture. Future research should explore interactions between leadership styles and organizational factors to maximize SMEs' innovative potential.